Coronary Intervention in ST-Segment Elevation Myocardial Infarction Patients With Symptom Onset >12 Hours: Data from China Acute Myocardial Infarction Registry. (February 2023) - Hu, Mengjin; Peng, Ya; Gao, Xiaojin; Yang, Jingang; Xu, Haiyan; Wu, Yuan; Song, Lei; Qiao, Shubin; Hu, Fenghuan; Wang, Yang; Li, Wei; Jin, Chen; et al.
To determine whether late percutaneous coronary intervention (PCI) of an infarct-related artery >12 h after ST-segment elevation myocardial infarction onset is beneficial, patients were included from the prospective, nationwide, multicenter China Acute Myocardial Infarction registry. The number of patients who underwent PCI or received drug therapy alone was 4791 and 1149, respectively. Hazard ratio (HR) and associated 95% confidence interval (CI) were calculated. Compared with drug therapy, PCI was associated with lower incidences of 2-year major adverse cardiac and cerebrovascular events (MACCE; 6.43 vs 20.19%; HR, .27; 95% CI, .23-.32; P < .001), all-cause death (4.13 vs 15.74%; HR, .24; 95% CI, .20-.30; P < .001), myocardial infarction (1.73 vs 3.31%; HR, .49; 95% CI, .33-.72; P = .0003), stroke (1.02 vs 2.00%; HR, .47; 95% CI, .28-.77; P = .0026), and revascularization (10.96 vs 27.56%; HR, .32; 95% CI, .26-.39; P < .001). Subgroup analysis consistently indicated that PCI was superior to drug therapy. Moreover, the left ventricular ejection fraction in the PCI group was increased after 2-year follow-up, whereas there was no significant increase in the drug therapy group. In conclusion, late PCI is common in Chinese clinical practice, and it is associated with significant improvements in cardiac function and survival compared with drug therapy alone.